SYNTHESIS AND CHARACTERIZATION OF POLY[(2-DIMETHYLAMINO)ETHYL METHACRYLATE]-PAN/TIO2 COMPOSITE CRYOGELS AND THEIR USE IN SEPARATION STUDY - Bütün Şengel, Sultan; Gökkuş, Kutalmış; Keyi̇k, Kübra; Bütün, Vural (Anadolu Universitesi Bilim ve Teknoloji Dergisi-A: Uygulamali Bilimler ve Muhendislik, 2021)
The aim of this study was to prepare high surface area nano-sized polyacrylonitrile (PAN) particles and their nanocomposite with TiO2 (PAN/TiO2) by using electrospraying method and to use it in super porous composite cryogel preparation using pH responsive monomer, 2-(dimethylamino)ethyl methacrylate. The cryogel composite was synthesized via cryogelation method by including the PAN/TiO2 nanoparticle within polymeric matrices before cryogelation. The cryogel system was preferred for the polymeric system because of its features such as its super-porous structure, shape retention, reusability, and its fast response to the application. In this way, an increase in performance is expected in separation and purification studies by creating synergy by processing nanoparticles into the macro system.
Keywords: Engineering; Mühendislik; Electrospraying; PAN/TiO2 nanocomposite; PDMA cryogel; separation and purification